Neuroendocrine Neoplasia in Extranodal Marginal Zone Lymphoma of Mucosa-Associated Lymphoid Tissue (MALT Lymphoma) of the Lung: A Case Report and Immunohistochemistry Analysis of Eight Pulmonary MALT Lymphomas. (October 2018) - Savari, Omid; Hastings, Hope; Rayes, Rania; Tomashefski, Joseph F.
Carcinoid tumorlets are peribronchiolar proliferations of neuroendocrine cells often associated with lung scars. Extranodal marginal zone lymphoma of mucosa-associated lymphoid tissue (MALT lymphoma) is a non-Hodgkin's lymphoma that frequently involves the gastrointestinal tract but less commonly is described in the lung. Simultaneous occurrence of neuroendocrine neoplasms and MALT lymphoma is extraordinarily rare and has predominately been reported in the gastrointestinal tract. In this article, we describe the case of a 73-year-old female with coexisting pulmonary MALT lymphoma and carcinoid tumorlets of the right middle lobe. Retrospective series of 8 pulmonary MALT lymphomas are evaluated for neuroendocrine neoplasia by immunohistochemistry. No correlation between MALT lymphoma and neuroendocrine neoplasia was identified in this case series. While the concurrence of these distinctive neoplasms is most likely coincidental, the presence of a common risk factor, or one neoplasm as a risk factor for the other, deserves study of a larger group of pulmonary MALT lymphomas.